Head-mounted augmented reality to support reassurance and social interaction for autistic children with severe learning disabilities - Bauer, Valentin; Bouchara, Tifanie; Duris, Olivier; Labossière, Charlotte; Clément, Marie-Noëlle; Bourdot, Patrick (Frontiers in Virtual Reality, 2023)
Augmented Reality (AR) is promising to complement autism approaches but has mainly focused on training socio-emotional abilities for autistic children with mild learning disabilities. To better consider autistic children with severe learning disabilities and complex needs (SLN), stakeholders advise using collaborative AR sensory-based mediation approaches. Magic Bubbles is a multisensory AR environment created based on stakeholders’ interviews, then adapted for a day hospital setting in collaboration with practitioners, and finally validated in terms of acceptability and usability for autistic children with SLN. In this paper, we report on our latest study that explores three main research questions: (1) To what extent can Magic Bubbles secure autistic children with SLN? (2) To what extent can Magic Bubbles prompt the dyadic relationship between an autistic child with SLN and a practitioner? (3) What is the overall quality of experience for autistic children with SLN when using Magic Bubbles? To answer these questions, seven autistic children with SLN participated in at least six weekly sessions over three months in a day hospital setting. Data collection and analysis used qualitative and quantitative methods, mainly drawing upon grounded theory to evaluate their experiences. Findings validate the three research questions, offer a detailed account of children's experiences with AR, and outline future directions.